Modified Glasgow prognostic score can predict survival of muscle invasive bladder cancer patients after radiotherapy. (22nd June 2020) - Kikuchi, Koyo; Nakamura, Ryuji; Segawa, Takafumi; Oikawa, Hirobumi; Ariga, Hisanori
Abstract: In patients with various cancers, modified Glasgow prognostic score (mGPS) before treatment has predicted prognoses after antitumor therapy. This study aimed to assess whether pretreatment mGPS also has predictive value in patients with muscle-invasive bladder cancer (MIBC) after radiotherapy. A retrospective review accumulated 98 consecutive MIBC patients treated with definitive 3D-conformal radiotherapy from January 2011 to December 2016 in a single center. It included cT2-4bN0-3M0 patients with a median age of 79 years (range: 49 to 95 years). Radiotherapy was delivered at 60–66 Gy for bladder cancer. Patients were categorized in terms of their pretreatment serum albumin and C-reactive protein (CRP) values as mGPS_0, mGPS_1, and mGPS_2. Among them, cumulative overall survival (OS) rates were compared by Kaplan–Meier plots with log-rank tests. The number of patients with mGPS_0, mGPS_1, and mGPS_2 were 40, 40, and 18, respectively. The median follow-up time for all patients was 19 months (range: 2–73 months). The 2-year OS rate for all patients was 75.7%. The 2-year OS rates for mGPS_0, mGPS_1, and mGPS_2 were 85.1%, 71.3%, and 60.9%, respectively. Kaplan–Meier curves revealed a significantly higher cumulative OS rate for mGPS_0 compared with mGPS_1 and mGPS_2 ( P = 0.003). Using multivariate Cox regression analysis, mGPS_0 and good performance status were associated with favorable OS rates, of which mGPS_0 was more significant (Hazard ratio 2.74, 95% CI 1.30–5.57, P = 0.008). Modified Glasgow prognostic score may be a novel biomarker that can predict survival in patients with MIBC after radiotherapy.